A new LNC89/LNC60-Col11a2 axis revealed by whole-transcriptome analysis may be associated with goiters related to excess iodine nutrition - Nie, Guanying; Li, Shuang; Zhang, Wei; Meng, Fangang; Ru, Zixuan; Li, Jiahui; Sun, Dianjun; Li, Ming (Frontiers in Endocrinology, 2024)
Goiter related to excessive iodine nutrition remains a significant public health issue in some countries. There has been no reported study on long noncoding RNAs (lncRNAs) related to goiters. In this study, goiter was induced by drinking water with excess iodine for 10 or 20 weeks in Kunming mice. Whole transcriptome sequencing results showed that LNC89 expression increased in mice goiter tissues compared to normal thyroid tissues and higher in 20 weeks goiter tissues than in 10 weeks goiter tissues, which were identified by qRT-PCR. Cooperate with human-mouse homologous gene conversion, a new LNC89 /LNC60-Col11a2 axis was predicted by LncTar and expression correlation analysis based on whole transcriptome sequencing results. Increased Col11a2 expression was also identified by qRT-PCR and Western blot in the mice goiter tissues. In the human normal thyroid cell line Nthy-ori-3 treated with KI03, LNC60 and Col11a2 expression increased with promoted cell viability, which were